2005
DOI: 10.1200/jco.2005.12.514
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Quality of Life Information to Cancer Patients: A Study of Six Presentation Formats

Abstract: Patients generally prefer a simple linear representation of group mean HRQL scores, and can accurately interpret data presented in this format more than 98% of the time irrespective of their age group and educational level. The findings have important implications for the communication of clinical trial HRQL results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
4
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(89 citation statements)
references
References 34 publications
1
81
4
3
Order By: Relevance
“…It is possible that HRQL data are more informative in surgical oncology trials where resection of the primary tumour, local nodes and surrounding tissues with or without reconstruction has an immediate negative impact on HRQL as well as relieving specific symptoms related to the primary tumour 26 . Where there is clinical equipoise, it is more likely that HRQL aspects will influence treatment choice, although the practicalities of imparting HRQL information to patients alongside survival and other clinical outcome data are complex 27 . Further work is needed in this area to develop best methods of explaining HRQL outcomes to patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that HRQL data are more informative in surgical oncology trials where resection of the primary tumour, local nodes and surrounding tissues with or without reconstruction has an immediate negative impact on HRQL as well as relieving specific symptoms related to the primary tumour 26 . Where there is clinical equipoise, it is more likely that HRQL aspects will influence treatment choice, although the practicalities of imparting HRQL information to patients alongside survival and other clinical outcome data are complex 27 . Further work is needed in this area to develop best methods of explaining HRQL outcomes to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, different ways of communicating HRQL to patients with lung cancer have been tested. It was found that most patients understand simple graphical presentations of mean quality-of-life scores [17]. More work is needed to train surgeons to understand and communicate HRQL and clinical outcomes to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients want information about the impact of treatment options on their HRQoL when making decisions about treatment [38,39] and are capable of interpreting HRQoL data when presented in simple formats [40]. When HRQoL data are presented to them in the decision-making process, it has been shown to influence their decisions about treatment options [41].…”
Section: Decision Aidsmentioning
confidence: 99%